Quantitative single shot and spatially resolved plasma wakefield diagnostics - Kasim, M; Norreys, P; Holloway, J; Trines, R (University of Oxford, 2015)
This dataset and scripts are used in producing the simulations and images in the "Quantitative single shot and spatially resolved plasma wakefield diagnostics" paper. This uses OSIRIS 431 2D.